Serum metabolites and hypercholesterolemia: insights from a two-sample Mendelian randomization study - Wang, Weitao; Qiao, Jingwen; Su, Zhaoyin; Wei, Hui; Wu, Jincan; Liu, Yatao; Lin, Rubing; Michael, Nerich (Frontiers in Cardiovascular Medicine, 2024)
Background Hypercholesterolemia, a critical contributor to cardiovascular disease, is not fully understood in terms of its relationship with serum metabolites and their role in disease pathogenesis. Methods This study leveraged GWAS data to explore the relationship between serum metabolites and hypercholesterolemia, pinpointing significant metabolites via Mendelian Randomization (MR) and KEGG pathway enrichment analysis. Data on metabolites were sourced from a European population, with analysis focusing on individuals diagnosed with hypercholesterolemia. Results Out of 486 metabolites analyzed, ten showed significant associations with hypercholesterolemia, categorized into those enhancing risk and those with protective effects. Specifically, 2-methoxyacetaminophen sulfate and 1-oleoylglycerol (1-monoolein) were identified as risk-enhancing, with odds ratios (OR) of 1.545 (95% CI: 1.230–1.939; P_FDR = 3E−04) and 1.462 (95% CI: 1.036–2.063; P_FDR = 0.037), respectively. On the protective side, 3-(cystein-S-yl)acetaminophen, hydroquinone sulfate, and 2-hydroxyacetaminophen sulfate demonstrated ORs of 0.793 (95% CI: 0.735–0.856; P_FDR = 6.18E−09), 0.641 (95% CI: 0.423–0.971; P_FDR = 0.042), and 0.607 (95% CI: 0.541–0.681; P_FDR = 5.39E−17), respectively. In addition, KEGG pathway enrichment analysis further revealed eight critical pathways, comprising “biosynthesis of valine, leucine, and isoleucine”, “phenylalanine metabolism”, and “pyruvate metabolism”, emphasizing their significant role in the pathogenesis of hypercholesterolemia. Conclusion This study underscores the potential causal links between particular serum metabolites and hypercholesterolemia, offering innovative viewpoints on the metabolic basis of the disease. The identified metabolites and pathways offer promising targets for therapeutic intervention and warrant further investigation.